Stories of change in nutrition in Burkina Faso 1992–2018: a macro-level perspective - Turowska, Zuzanna; Buttarelli, Emilie; Sombie, Issa; Nisbett, Nicholas; van den Bold, Mara; Becquey, Elodie (Springer, 2023)
Looking back at the development of successful enabling environments for nutrition may inform policymakers on how to accelerate progress to end all forms of malnutrition by 2030. As under-five stunting declined substantially in Burkina Faso, from a peak at 45% in 1998/99 to 25% in 2018, we analyzed through a stories of change approach the actors, ideas, initiatives, policies and capacities which enabled wide-scale nutrition progress. We triangulated findings from policy analysis, stakeholder mapping, and national-level semi-structured interviews (n = 20). We found that since 2002, nutrition has been anchored in the Ministry of Health, where leadership advocated for the creation of coordination bodies, enabling a coherent defining of nutrition and laying groundwork for better integration of nutrition into and prioritization of nutrition by the health and tangential ministries. Under the leadership of the Ministry of Health and its partners, horizontal and vertical coherence in nutrition action increased, through effective cooperation between nutrition actors; increasing intersectoral collaboration, particularly with the influential agriculture sector; and increasing funding to support nutrition-sensitive programming and build the capacity of nutrition staff. Nevertheless, sustainably organizing funding and human resources at the decentralized level remained challenging, in a context of emerging threats such as climate change and insecurity. Burkina Faso’s health sector’s success in creating an enabling environment for nutrition may have contributed to improvements in child nutrition alongside other sectoral improvements. Enhancing accountability of the Health, Agriculture, WASH, Education and Social Protection sectors and empowering decentralized bodies to take nutrition-relevant decisions may help accelerating progress in nutrition.